Neonatal Perforated Appendicitis Masquerading as Necrotizing Enterocolitis - Tumen, Andrew; Chotai, Pranit N; Williams, John Matthew; Myers-Webb, Adrianne; Zhang, Jie; Krishnan, Ramesh; Eubanks III, James W (Journal of Neonatal Surgery, 2017)
A preterm neonate underwent emergent laparotomy for presumed necrotizing enterocolitis (NEC). Intra-operatively, neonatal perforated appendicitis (NPA) was encountered. This may represent a form of NEC localized to the appendix. A high index of clinical suspicion and early laparotomy are recommended.